On the Psychodynamics of Wearing a Headscarf Among Young Muslim Women Living in Germany—New Heterogeneous Poles of Subjectivity - Lena Barth; Kostja Wacker; Necip Yurddas; Paul Kaiser; Gonca Tuncel-Langbehn; Barbara Ruettner; Lutz Goetzmann (Journal of International Migration and Integration, 2024)
The wearing of a headscarf and the veiling especially of the female face or the whole body is a universal phenomenon that occurs in different eras and in different regions and cultures. Today, wearing a headscarf has become a symbol of Islam, especially in Western countries, and is often met with Islamophobic rejection. In our study, using a qualitative interview, we questioned 25 young Muslim women of Turkish origin (between 18 and 25~years old, n 0.167em=0.167em25) living in Germany about their reasons for wearing or not wearing a headscarf and their experiences on account of this decision. The majority ( n 0.167em=0.167em16) of the predominantly academically educated female participants do not wear a headscarf, primarily for reasons of female attractiveness, an internalized religiosity, and as an expression of the disintegration of the family hierarchy. All female respondents ( n 0.167em=0.167em7) from families with divorced parents do not wear headscarves, while for the other female respondents ( n 0.167em=0.167em9) who do not wear headscarves, the family seems to have a more liberal mindset. Reasons for wearing a headscarf are especially a religious attachment to Islam, fashionable self-confidence, and the wish to combine Western emancipation with the traditional dress code (in the form of a hybrid identity). These findings are considered against the background of a psychoanalytic reading of the Quranic suras on veiling (according to F. Benslama) and the Lacanian dialectic of the imaginary and symbolic phallus. The diversity of personal reasons can be described with the concept of a heterogeneous subjectivity, which arises from the clash of Western secular and Turkish-Islamic notions.
Keywords: 300; Headscarves; Veiling; Islam; Migration; Imaginary phallus; Symbolic phallus